Charge-convertible pH-sensitive lignin-based antibacterial nanoparticles as well as preparation method and application thereof
By grafting positively charged antibacterial active substances on lignin and making their surface charge convertible, forming pH-sensitive lignin-based antibacterial nanoparticles with charge convertible, the problem of poor antibacterial effect of existing lignin antibacterial materials on biofilms is solved, and more efficient antibacterial effect and biocompatibility are achieved.
Patent Information
- Application Number
- CN202411608631.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The existing lignin antibacterial materials have poor antibacterial effects on biofilms, and the preparation process is complex and costly.
A charge-convertible pH-sensitive lignin-based antibacterial nanoparticles were designed to form a nanocarrier by grafting positively charged antibacterial active substances on lignin and making their surface charges convertible.
The antibacterial activity and biocompatibility of lignin are significantly improved, allowing nanoparticles to gradually penetrate the mucus barrier and biofilm in the biofilm environment and directly reach the dosing site to achieve better antibacterial effects.
Smart Images

Figure CN119505250A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lignin-based functional materials, and in particular relates to charge-convertible pH-sensitive lignin-based antibacterial nanoparticles, and a preparation method and application thereof. Background Art
[0002] Infections caused by pathogenic bacteria have become an important cause of death, with approximately 700,000 deaths worldwide each year. More than 60% of human infectious diseases can be attributed to bacterial biofilms, such as chronic bacterial prostatitis, chronic otitis media, and osteomyelitis. It is generally believed that biofilms and their surrounding environment are acidic and highly reducing. For example, the pH of the methicillin-resistant Staphylococcus aureus (MRSA) biofilm microenvironment can reach 5.5 or even lower. It is imperative to use the specific microenvironment of biofilms to study the design of strategies to combat biofilm infections, especially those caused by drug-resistant bacteria. Site-specific drug delivery is an attractive strategy that can achieve higher drug concentrations and fewer side effects. However, drugs must first overcome a series of barriers, including airway mucus and biofilm matrix, before they come into contact with bacteria. In recent studies, cationic nanoparticles have shown advantages in penetrating biofilms. In contrast, particles that maintain a neutral or slightly negative charge are more conducive to penetrating mucus because they are able to minimize adverse interactions with mucin.
[0003] Lignin is the second largest biomass resource in the plant kingdom after cellulose. It is an amorphous biopolymer with a three-dimensional network structure formed by phenylpropane units connected to each other through ether bonds and CC bonds. Since lignin is rich in various active functional groups such as phenolic hydroxyl, alcoholic hydroxyl, methoxy, benzene ring, etc., it can participate in oxidation, reduction, hydrolysis, alcoholysis, acidolysis, photolysis, acylation, sulfonation, esterification, halogenation, nitration, polycondensation and other reactions, so that its application field is expanded. It is considered to be a natural antibacterial material with good biological activity, but the antibacterial effect of relying solely on the biological activity of lignin itself is limited. Patent CN115926206 A discloses a lignin nanoparticle and its preparation method and application, which relates to the technical field of antibacterial materials. The invention uses only lignin as a raw material, and uses an organic solvent to grade the lignin, achieving the distribution adjustment of molecular weight and chemical structure, and then dissolving the graded lignin in a mixed solvent of an organic solvent and water, adding it dropwise to distilled water at a uniform speed under stirring conditions or adding distilled water dropwise to the graded lignin solution at a uniform speed, and then rotary evaporation and drying to obtain lignin nanoparticles. More active functional groups (phenolic hydroxyl and carboxyl) are exposed in the whole process, solving the problems of resource waste and low-value utilization caused by the dispersibility and structural heterogeneity of lignin, and the problems that the existing lignin antibacterial materials mostly use composite materials, the preparation process is complicated, and the cost is high. However, the antibacterial effect of the above antibacterial materials on the antibacterial activity of lignin itself is very limited. Chemical modification of lignin to obtain a lignin-based composite antibacterial material with stronger antibacterial biological activity is an effective method. Patent CN 118435941 A discloses a method for preparing a lignin-nanosilver composite antibacterial agent. The binary composite solvent obtained by compounding water and an organic solvent miscible with water is used as the reaction solvent in the preparation process, and the usable solvents are expanded from strong polar solvents such as dimethylamide to weak polar solvents such as tetrahydrofuran, which facilitates the synthesis of lignin-nanosilver composite antibacterial agents, and the synthesized lignin-nanosilver composite antibacterial agents have small particle size, good storage stability, good antibacterial activity, and low cytotoxicity; thus solving the technical problem of the lack of a synthetic method for lignin-nanosilver composite antibacterial agents in the prior art. Patent CN 111743862 A discloses multi-bioactive modified lignin self-assembled drug-loaded nanomicelles and a preparation method thereof. Lignin is prepared by acylation, esterification and other reactions to prepare lignin grafted bioactive compounds, and then prepared into nanomicelles. The nanomicelles are used as good drug carriers and also have multiple biological activities of lignin and bioactive compounds.
[0004] In summary, for bacterial biofilms, it is urgent to develop a lignin-based composite antibacterial material that has high antibacterial biological activity, biocompatibility and safety, and can successfully penetrate the mucus barrier and biofilm and reach the drug delivery site. Summary of the invention
[0005] The purpose of the present invention is to solve the problem that the original lignin has poor antibacterial effect on biofilms, and a charge-convertible pH-sensitive lignin-based antibacterial nanoparticle is designed, which is a nanoparticle responsive to the microenvironment of the biofilm. The positively charged antibacterial active substance is grafted onto the lignin to make its charge convertible, and is prepared into a nanocarrier. The present invention can improve the dispersibility of lignin, improve the antibacterial activity, biocompatibility and safety of lignin, and at the same time, the surface charge sensitive to pH changes enables the nanoparticles to gradually penetrate the mucus barrier and biofilm, directly reach the administration site, and achieve a better antibacterial effect on the biofilm.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing charge-switchable pH-sensitive lignin-based antibacterial nanoparticles comprises the following steps:
[0008] S1. dissolving polyallylamine (PAH) in dimethyl sulfoxide (DMSO) to obtain solution A; dissolving lignin in dimethyl sulfoxide to obtain solution B;
[0009] S2. Add the solution B dropwise to the solution A, and then add a carboxyl activator 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) and a catalyst triethylamine (TEA) to carry out a first reaction to obtain a first reaction solution; through this step, the positively charged polyallylamine is grafted onto lignin through an amide reaction to increase the positive charge density of the lignin, thereby preparing a lignin-polyallylamine (LP) conjugate.
[0010] S3. Add anhydride to the first reaction solution, carry out a second reaction, and then dialyze and freeze-dry to obtain a lignin-polyallylamine-anhydride (LPD) conjugate; through this step, the anhydride is grafted onto the positively charged LP conjugate to obtain an acid-stimulation-responsive LPD conjugate, which has a negative charge with higher biocompatibility on the one hand, and can undergo charge conversion to become positive in a slightly acidic environment on the other hand.
[0011] S4. The lignin-polyallylamine-anhydride conjugate obtained in step S3 is dissolved in dimethyl sulfoxide, and the resulting solution is added dropwise to water or water is added dropwise to the resulting solution under stirring to obtain solution C, and dialyzed to obtain charge-convertible pH-sensitive lignin-based nanoparticles (LP-DNPs), wherein the size of the obtained LP-DNPs is between 300 and 400 nm; the LPD conjugate is prepared into nanoparticles using an anti-solvent method to increase the dispersibility of the conjugate.
[0012] In step S1, the polyallylamine is prepared by the following method: dissolving polyallylamine hydrochloride and sodium hydroxide in water, dialyzing, and freeze-drying to obtain;
[0013] Among them, the addition amount of the polyallylamine hydrochloride is 10-80g / L; the addition amount of the sodium hydroxide is 10-50g / L; the dialysis bag used in the dialysis has a molecular weight cutoff of 15-20kDa, the dialysis fluid used is water, and the dialysis time is 3-7 days; the freeze-drying temperature is -55--80°C, and the time is 2-3 days.
[0014] In step S1, the lignin is any one of alkali lignin, fractionated lignin, gramineous lignin, broadleaf lignin, coniferous lignin and acid-precipitated lignin; the concentration of solution A is 4 to 100 g / L; the concentration of solution B is 10 to 100 g / L.
[0015] In step S2, the solution B is added dropwise to the solution A to control the mass ratio of polyallylamine to lignin to be 1:1 to 1:20; the concentrations of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and triethylamine in the mixed solution of the solution A and the solution B are 1 to 10 g / L and 1 to 5 μL / mL, respectively.
[0016] In step S2 and step S3, the first reaction or the second reaction is carried out under the conditions of stirring at 25 to 35° C. for 24 to 48 hours.
[0017] In step S3, the acid anhydride is maleic anhydride or dimethylmaleic anhydride; the mass ratio of the acid anhydride to the lignin is 1:10 to 1:150; the dialysis bag used in the dialysis has a molecular weight cutoff of 15 kDa, the dialysis fluid used is dimethyl sulfoxide, and the dialysis time is 3 to 5 days; the freeze-drying temperature is -55 to -80°C, and the time is 2 to 3 days.
[0018] In step S4, the stirring condition is a rotation speed of 200 to 800 rpm, and the dripping time is controlled at 10 to 200 min; in the solution C, the concentration of the lignin-polyallylamine-anhydride coupling is 0.1 to 5 mg / mL; the volume ratio of dimethyl sulfoxide to water is 4:1 to 40; the dialysis, the dialysis bag used has a molecular weight cutoff of 15 to 20 kDa, the dialysate used is water, and the dialysis time is 24 to 72 h.
[0019] The application of the charge-switchable pH-sensitive lignin-based nanoparticles in the preparation of antibacterial products.
[0020] Wherein, the product is a medicine or a drug carrier; the antibacterial agent is antibacterial itself or antibacterial biofilm.
[0021] The bacteria include Escherichia coli, Staphylococcus aureus, Monilia albican, Listeria monocytogenes and Pseudomonas aeruginosa.
[0022] Beneficial effects:
[0023] (1) The preparation method of the present invention is simple, fast and environmentally friendly. Lignin is chemically coupled with polyallylamine and anhydride through an efficient, convenient and stable synthesis system. The synthesized lignin-based nanoparticles can be stably dispersed and uniformly dispersed in water and have uniform particle size.
[0024] (2) The charge-convertible pH-sensitive lignin-based antibacterial nanoparticles of the present invention are nanoparticles that respond to biofilm microenvironmental stimulation, with positively charged antibacterial active substances grafted onto lignin, and their surface charges are convertible. Not only does it significantly improve the antibacterial activity of lignin, but the surface charge that is sensitive to pH changes makes the nanoparticles positively charged in the biofilm environment (slightly acidic), allowing them to better bind to negatively charged bacteria and gradually penetrate the mucus barrier and biofilm to reach the site of administration, achieving a better antibacterial effect. When applied in the antibacterial field, it can effectively inhibit the growth of biofilms and have a clearing effect on biofilms that have already been generated. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.
[0026] Figure 1 is a particle size distribution diagram of the charge-switchable pH-sensitive lignin-based nanoparticles of the present invention;
[0027] Figure 2 The infrared spectra of the charge-switchable pH-sensitive lignin-based nanoparticles and lignin alone of the present invention, wherein LPD represents lignin-polyallylamine (LPD) conjugate, LP represents lignin-polyallylamine conjugate, and L represents lignin;
[0028] Figure 3 is the pH-sensitive charge convertibility of the charge-convertible pH-sensitive lignin-based nanoparticles in Example 7;
[0029] Figure 4 is the antibacterial activity of the charge-switchable pH-sensitive lignin-based nanoparticles in Example 8;
[0030] Figure 5 The biofilm inhibition effect of the charge-switchable pH-sensitive lignin-based nanoparticles in Example 9 and the crystal violet staining picture of the biofilm at pH=5;
[0031] Figure 6 The biofilm removal effect of the charge-switchable pH-sensitive lignin-based nanoparticles in Example 10 and the crystal violet staining picture of the biofilm at pH=5;
[0032] Figure 7 This is the in vitro release curve of the pH-sensitive lignin-based nanoparticles loaded with curcumin in Example 11. DETAILED DESCRIPTION
[0033] The present invention is further described below according to the following examples. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention. Without departing from the spirit and essence of the present invention, modifications or substitutions made to the method, steps or conditions of the present invention all belong to the scope of the present invention.
[0034] If the specific techniques or conditions are not specified in the examples, they are carried out according to the techniques or conditions described in the literature in the field or according to the product instructions. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased through regular channels.
[0035] Table 1 shows the elemental analysis of charge-convertible lignin-based nanoparticles and lignin alone. It can be seen from the table that the N content of lignin increased significantly after PAH modification, which further confirms the increase in the amino content of lignin after modification.
[0036] Table 1 Elemental analysis of charge-switchable lignin-based nanoparticles and lignin alone
[0037]
[0038] Example 1
[0039] 374 mg of PAH·HCl and 200 mg of NaOH were weighed and dissolved in 5 mL of distilled water. The resulting solution was placed in a dialysis bag (15 kDa), dialyzed in distilled water for 3 days, and freeze-dried at -80°C for 3 days to obtain PAH.
[0040] Weigh 20 mg of PAH and completely dissolve it in 5 mL of DMSO. Stir and dissolve it at 25 °C and pour it into a three-necked round-bottom flask. Then, completely dissolve 100 mg of alkali lignin in 10 mL of DMSO and evenly drop it into the three-necked round-bottom flask. Finally, add 20 mg of EDC and 15 μL of TEA into the three-necked round-bottom flask and stir and react at 25 °C for 24 h. After the reaction, add 2 mg of dimethyl maleic anhydride (DMMA) to the three-necked round-bottom flask and continue to stir and react at 25 °C for 24 h. After the reaction, place the product in a dialysis bag (15 kDa), dialyze it in DMSO for 3 days, and freeze-dry it at -80 °C for 3 days to obtain the product LPD conjugate.
[0041] 150 mg of LPD conjugate dissolved in 15 mL of DMSO was added to 135 mL of distilled water at a stirring speed of 800 rpm at a rate of 10 mL / min, and the final concentration of LPD conjugate was 1 mg / mL. The solution was transferred to a dialysis bag (15 kDa) and dialyzed in distilled water for 72 h to remove DMSO. Finally, charge-switchable pH-sensitive lignin-based nanoparticles were formed. Figure 1 This is a particle size distribution diagram of charge-convertible pH-sensitive lignin-based nanoparticles. It can be seen from the figure that the average particle size is between 300 and 400 nm.
[0042] Figure 2 The infrared spectra of charge-convertible pH-sensitive lignin-based nanoparticles and lignin alone are shown in Figure 1. In the figure, LPD represents lignin-polyallylamine-dimethylmaleic anhydride conjugate, LP represents lignin-polyallylamine conjugate, and L represents lignin. Through infrared spectroscopy analysis, it was determined that the carboxyl group of lignin reacted with the amine group of PAH to synthesize the LP conjugate. Figure 2 As shown in Figure 2, the stretching vibration of the aliphatic hydroxyl group and the phenolic hydroxyl group of lignin is at 3410 cm -1 The CH stretching vibrations of lignin methyl and methylene correspond to 2935 cm -1 and 2840cm -1 1600, 1510 and 1430cm -1 The three absorption peaks at 1704 cm-1 correspond to the benzene ring structure of lignin. -1 The original characteristic absorption peak of the carboxyl group was weakened. Further, by reacting DMMA with the remaining amine groups of PAH to form an acid-sensitive chemical bond, the absorption peak of C=O introduced by DMMA appeared at 1700cm -1 .
[0043] Example 2
[0044] 374 mg of PAH·HCl and 200 mg of NaOH were weighed and dissolved in 5 mL of distilled water. The resulting solution was placed in a dialysis bag (20 kDa), dialyzed in distilled water for 3 days, and freeze-dried at -80°C for 3 days to obtain PAH.
[0045] Weigh 20 mg of PAH and completely dissolve it in 5 mL of DMSO. Stir and dissolve it at 25 °C and pour it into a three-necked round-bottom flask. Then, completely dissolve 200 mg of alkali lignin in 10 mL of DMSO and evenly drop it into the three-necked round-bottom flask. Finally, add 20 mg of EDC and 15 μL of TEA into the three-necked round-bottom flask and stir and react at 25 °C for 24 h. After the reaction, add 2 mg of dimethyl maleic anhydride (DMMA) to the three-necked round-bottom flask and continue to stir and react at 25 °C for 24 h. After the reaction, place the product in a dialysis bag (15 kDa), dialyze it in DMSO for 3 days, and freeze-dry it at -80 °C for 3 days to obtain the product LPD conjugate.
[0046] 150 mg of LPD conjugate dissolved in 15 mL of DMSO was added to 135 mL of distilled water at a stirring speed of 800 rpm at a rate of 10 mL / min, and the final concentration of LPD conjugate was 1 mg / mL. The solution was transferred to a dialysis bag (20 kDa) and dialyzed in distilled water for 36 h to remove DMSO. Finally, charge-switchable pH-sensitive lignin-based nanoparticles were formed.
[0047] Example 3
[0048] 250 mg of PAH·HCl and 200 mg of NaOH were weighed and dissolved in 5 mL of distilled water. The resulting solution was placed in a dialysis bag (15 kDa), dialyzed in distilled water for 3 days, and freeze-dried at -80°C for 3 days to obtain PAH.
[0049] Weigh 20 mg of PAH and completely dissolve it in 5 mL of DMSO. Stir and dissolve it at 25 °C and pour it into a three-necked round-bottom flask. Then, completely dissolve 200 mg of alkali lignin in 10 mL of DMSO and evenly drop it into the three-necked round-bottom flask. Finally, add 20 mg of EDC and 15 μL of TEA into the three-necked round-bottom flask and stir and react for 24 h at 25 °C. After the reaction, add 2 mg of dimethyl maleic anhydride (DMMA) to the three-necked round-bottom flask and continue to stir and react for 24 h at 25 °C. After the reaction, place the product in a dialysis bag (15 kDa), dialyze it in DMSO for 3 days, and freeze-dry it at -80 °C for 2 days to obtain the product LPD conjugate.
[0050] 150 mg of LPD conjugate dissolved in 15 mL of DMSO was added to 135 mL of distilled water at a stirring speed of 800 rpm at a rate of 10 mL / min, and the final concentration of LPD conjugate was 1 mg / mL. The solution was transferred to a dialysis bag (15 kDa) and dialyzed in distilled water for 72 h to remove DMSO. Finally, charge-switchable pH-sensitive lignin-based nanoparticles were formed.
[0051] Example 4
[0052] 250 mg of PAH·HCl and 200 mg of NaOH were weighed and dissolved in 5 mL of distilled water. The resulting solution was placed in a dialysis bag (15 kDa), dialyzed in distilled water for 3 days, and freeze-dried at -80°C for 3 days to obtain PAH.
[0053] 30 mg of PAH was weighed and completely dissolved in 5 mL of DMSO, stirred and dissolved at 25 ° C, and then poured into a three-necked round-bottom flask; then, 200 mg of alkali lignin was completely dissolved in 10 mL of DMSO and evenly added dropwise to the three-necked round-bottom flask; finally, 20 mg of EDC and 15 μL of TEA were added to the three-necked round-bottom flask and stirred and reacted at 25 ° C for 24 h. After the reaction was completed, 2 mg of dimethyl maleic anhydride (DMMA) was added to the three-necked round-bottom flask, and the reaction was continued to stir at 25 ° C for 24 h. After the reaction was completed, the product was placed in a dialysis bag (15 kDa), dialyzed in DMSO for 3 days, and freeze-dried at -80 ° C for 2 days to obtain the product LPD conjugate.
[0054] 200 mg of LPD conjugate dissolved in 15 mL of DMSO was added to 135 mL of distilled water at a stirring speed of 800 rpm at a rate of 10 mL / min, and the final concentration of LPD conjugate was 1.33 mg / mL. The solution was transferred to a dialysis bag (15 kDa) and dialyzed in distilled water for 72 h to remove DMSO. Finally, charge-switchable pH-sensitive lignin-based nanoparticles were formed.
[0055] Example 5
[0056] 374 mg of PAH·HCl and 200 mg of NaOH were weighed and dissolved in 5 mL of distilled water. The resulting solution was placed in a dialysis bag (15 kDa), dialyzed in distilled water for 3 days, and freeze-dried at -80°C for 3 days to obtain PAH.
[0057] 30 mg of PAH was weighed and completely dissolved in 5 mL of DMSO, stirred and dissolved at 25 ° C, and then poured into a three-necked round-bottom flask; then, 200 mg of fractionated lignin was completely dissolved in 10 mL of DMSO and evenly added dropwise to the three-necked round-bottom flask; finally, 20 mg of EDC and 15 μL of TEA were added to the three-necked round-bottom flask and stirred and reacted at 25 ° C for 24 h. After the reaction was completed, 2 mg of dimethylmaleic anhydride (DMMA) was added to the three-necked round-bottom flask, and the reaction was continued to stir at 25 ° C for 24 h. After the reaction was completed, the product was placed in a dialysis bag (15 kDa), dialyzed in DMSO for 3 days, and freeze-dried at -80 ° C for 2 days to obtain the product LPD conjugate.
[0058] 200 mg of LPD conjugate dissolved in 15 mL of DMSO was added to 135 mL of distilled water at a stirring speed of 800 rpm at a rate of 10 mL / min, and the final concentration of LPD conjugate was 1.33 mg / mL. The solution was transferred to a dialysis bag (15 kDa) and dialyzed in distilled water for 72 h to remove DMSO. Finally, charge-switchable pH-sensitive lignin-based nanoparticles were formed.
[0059] Example 6
[0060] 374 mg of PAH·HCl and 200 mg of NaOH were weighed and dissolved in 5 mL of distilled water. The resulting solution was placed in a dialysis bag (15 kDa), dialyzed in distilled water for 3 days, and freeze-dried at -80°C for 3 days to obtain PAH.
[0061] 30 mg of PAH was weighed and completely dissolved in 5 mL of DMSO, stirred and dissolved at 25 ° C, and then poured into a three-necked round-bottom flask; then, 100 mg of fractionated lignin was completely dissolved in 10 mL of DMSO and evenly added dropwise to the three-necked round-bottom flask; finally, 20 mg of EDC and 15 μL of TEA were added to the three-necked round-bottom flask and stirred and reacted at 25 ° C for 24 h. After the reaction was completed, 2 mg of dimethyl maleic anhydride (DMMA) was added to the three-necked round-bottom flask, and the reaction was continued to stir at 25 ° C for 24 h. After the reaction was completed, the product was placed in a dialysis bag (15 kDa), dialyzed in DMSO for 3 days, and freeze-dried at -80 ° C for 2 days to obtain the product LPD conjugate.
[0062] 200 mg of LPD conjugate dissolved in 15 mL of DMSO was added to 135 mL of distilled water at a stirring speed of 800 rpm at a rate of 10 mL / min, and the final concentration of LPD conjugate was 1.33 mg / mL. The solution was transferred to a dialysis bag (15 kDa) and dialyzed in distilled water for 72 h to remove DMSO. Finally, charge-switchable pH-sensitive lignin-based nanoparticles were formed.
[0063] Example 7
[0064] Taking the lignin-based nanoparticles prepared in Example 1 as an example, the charge conversion property of the lignin-based nanoparticles of the present invention was evaluated. The environmental pH values of the nanoparticles dispersed in the aqueous solution were adjusted to 7 and 5, respectively, and the nanoparticles were incubated at 37° C. and 200 rpm for 180 min, and the changes in the surface Zeta potential of the nanoparticles under the two pH conditions were measured. Figure 3 The pH-sensitive charge conversion of the charge-switchable pH-sensitive lignin-based nanoparticles is Figure 3 It can be seen that when the nanoparticles are in an environment with pH = 5, the charge changes from negative to positive after 10 minutes. In a neutral environment with pH = 7, the charge remains negative.
[0065] Example 8
[0066] The nanoparticle dispersion prepared in Example 1 was concentrated to 15 mg / mL by rotary evaporation, and then diluted with LB liquid medium at pH = 5 to concentrations of 0, 0.625, 1.25 and 2.5 mg / mL, respectively. Escherichia coli was then inoculated into the above medium and incubated for 2 h, and then the bacterial solution was taken out from each medium and diluted 10 9 The solution was spread on an LB plate and cultured at 37°C until colonies grew on the LB plate. The colonies were then counted to test the antibacterial effect of the lignin-based nanoparticles in a short period of time. The above is the construction process of the pH = 5 experimental group. At the same time, a control group of pH = 7 was constructed, and the operation steps were the same as those of the pH = 5 experimental group. Figure 4 The antibacterial activity of charge-convertible lignin-based nanoparticles can be seen from the figure. As the concentration of nanoparticles increases, the surface charge of the nanoparticles is converted to positive charge in a slightly acidic environment, which inhibits the growth of more E. coli. When the concentration is 2.5 mg / mL, the inhibition rate can reach 100%. In a neutral environment, the antibacterial effect is not obvious because the nanoparticles remain negatively charged.
[0067] Example 9
[0068] Use LB liquid medium with pH = 5 to dilute the Staphylococcus aureus culture solution to OD 600The concentration of the nanoparticles in Example 1 was 0.05, and the nanoparticle dispersion obtained in Example 1 was concentrated by rotary evaporation to 15 mg / mL, and then the concentration of the nanoparticles was adjusted with LB liquid culture medium at pH=5, and then the nanoparticle dispersion after concentration adjustment was added to the diluted bacterial solution, so that the bacterial solution concentrations of the nanoparticles in the bacterial solution were 0, 0.3, 0.6, 1.25 and 2.5 mg / mL respectively. Then the above bacterial solution was inoculated in a 96-well plate, and the biofilm at the bottom of the 96-well plate was rinsed with PBS after incubation at 37°C for 24 hours. Subsequently, 0.1% crystal violet aqueous solution (1g / L) was used for staining for 30 minutes, and after staining, the well plate was rinsed with PBS until the supernatant was colorless. Finally, 200 μL of 95% ethanol aqueous solution was added to dissolve the crystal violet and the absorbance was measured at 570nm. The crystal violet content represented by the absorbance indicated the amount of biofilm formed. The above is the construction process of the experimental group of pH=5. At the same time, a control group of pH=7 was constructed, and the operation steps were the same as those of the experimental group of pH=5. Figure 5 The biofilm inhibition effect of charge-convertible lignin-based nanoparticles and the crystal violet staining image of the biofilm at pH = 5 are shown. Figure 5 It is shown that in a slightly acidic environment (pH=5), the nanoparticles have a better inhibitory effect on biofilm than in neutral conditions, and the inhibition rate can reach up to 44% because the nanoparticles are positively charged after charge conversion.
[0069] Example 10
[0070] The Staphylococcus aureus solution was diluted to OD 600 The concentration of the nanoparticles was 0.05, and the nanoparticles were inoculated in a 96-well plate and incubated at 37°C for 24 hours. The nanoparticle dispersion prepared in Example 1 was concentrated to 15 mg / mL by rotary evaporation, and the concentration of the nanoparticles was adjusted with LB liquid culture medium at pH = 5. The nanoparticle dispersion after concentration adjustment was added to the bacterial solution incubated for 24 hours in the 96-well plate, so that the concentrations of the nanoparticles in the culture medium of the 96-well plate were 0, 0.3, 0.6, 1.25 and 2.5 mg / mL, respectively, and then continued to be incubated together for 24 hours. After the incubation, the biofilm at the bottom of the 96-well plate was rinsed with PBS. Subsequently, 0.1% crystal violet was used for staining for 30 minutes, and after the staining, the plate was rinsed with PBS until the supernatant was colorless. Finally, 200 μL of 95% ethanol was added to dissolve the crystal violet and the absorbance was measured at 570 nm. The crystal violet content represented by the absorbance indicated the amount of biofilm. The above is the construction process of the experimental group with pH = 5. At the same time, a control group with pH = 7 was constructed, and the operation steps were the same as those of the experimental group with pH = 5. Figure 6 The biofilm removal effect of charge-switchable lignin-based nanoparticles is shown in Figure 2. Figure 6The results show that the removal rate of nanoparticles in a neutral environment can reach up to 76%, and the removal rate in a slightly acidic environment can reach up to 82%. The experimental results prove that the nanoparticles of the present invention can effectively remove biofilms, and the removal effect on biofilms in an acidic environment is better than that in a neutral environment, and the removal rate is about 1.1 times that of a neutral environment.
[0071] Embodiment 11
[0072] 100 mg of curcumin and 200 mg of LPD were mixed in 10 mL of DMSO to obtain a mixed solution. The mixed solution was added to 90 mL of distilled water at a stirring speed of 800 rpm at a speed of 10 mL / min by the anti-solvent method to prepare LP-DNPs loaded with curcumin. The solution was transferred to a dialysis bag (15 kDa) and dialyzed in distilled water for 72 h to remove DMSO and free curcumin. Finally, charge-convertible pH-sensitive lignin-based nanoparticles (LP-DCNPs) loaded with curcumin were formed, and the drug encapsulation efficiency was 48%. The drug release behavior of lignin nanoparticles loaded with curcumin in a simulated in vivo slightly acidic environment was studied by dialysis. 1mL of LP-DCNPs dispersion with a concentration of 1mg / mL was added to a dialysis bag (MWCO=500Da), and then the dialysis bag was immersed in 50mL of 0.01M PBS (pH 5.0) release medium, and oscillated in a constant temperature shaker at 37°C, 200rpm / min, and 2mL of PBS release medium was taken as samples at 0h, 20min, 40min, 2h, 3h, 10h and 24h, respectively, and an equal volume of fresh PBS release medium was added to the sample. The sample absorbance value was detected at a wavelength of 428nm using an ultraviolet spectrophotometer, and the concentration of curcumin in the sample was calculated by substituting the standard curve. The in vitro release experiment was repeated 3 times in parallel. Figure 7 is the in vitro release curve of the pH-sensitive lignin-based nanoparticles loaded with curcumin in this example, Figure 7 It can be seen that when the sustained-release time is 10 hours, the cumulative release of curcumin basically reaches the maximum of 29.4%, and the release amount remains basically unchanged at the 24th hour.
[0073] The present invention provides a method for preparing charge-convertible pH-sensitive lignin-based nanoparticles and a method for applying the same. There are many methods and approaches to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention. All components not specified in this embodiment can be implemented using existing technologies.
Claims
1. A method for preparing charge-convertible pH-sensitive lignin-based antibacterial nanoparticles, characterized in that: The following steps are involved: S1. dissolving polyallylamine in dimethyl sulfoxide to obtain solution A; Dissolving lignin in dimethyl sulfoxide to obtain solution B; S2. adding the solution B dropwise to the solution A, and then adding 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and triethylamine to carry out a first reaction to obtain a first reaction solution; S3. adding anhydride to the first reaction solution, performing a second reaction, and then dialyzing and freeze-drying to obtain a lignin-polyallylamine-anhydride conjugate; S4. The lignin-polyallylamine-anhydride conjugate obtained in step S3 is dissolved in dimethyl sulfoxide, and the resulting solution is added dropwise to water or water is added dropwise to the resulting solution under stirring to obtain solution C, which is dialyzed to obtain charge-convertible pH-sensitive lignin-based nanoparticles.
2. The preparation method according to claim 1, characterized in that: In step S1, the polyallylamine is prepared by the following method: dissolving polyallylamine hydrochloride and sodium hydroxide in water, dialyzing, and freeze-drying to obtain the polyallylamine.
3. The preparation method according to claim 2, characterized in that: The amount of polyallylamine hydrochloride added is 10 to 80 g / L; the amount of sodium hydroxide added is 10 to 50 g / L; the molecular weight cutoff of the dialysis bag used in the dialysis is 15 to 20 kDa, the dialysis fluid used is water, and the dialysis time is 3 to 7 days; the freeze-drying temperature is -55 to -80°C and the time is 2 to 3 days.
4. The preparation method according to claim 1, characterized in that: In step S1, the lignin is any one of alkali lignin, fractionated lignin, gramineous lignin, broadleaf lignin, coniferous lignin and acid-precipitated lignin; the concentration of solution A is 4 to 100 g / L; the concentration of solution B is 10 to 100 g / L.
5. The preparation method according to claim 1, characterized in that: In step S2, the solution B is added dropwise to the solution A to control the mass ratio of polyallylamine to lignin to be 1:1 to 1:20; the concentrations of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and triethylamine in the mixed solution of the solution A and the solution B are 1 to 10 g / L and 1 to 5 μL / mL, respectively.
6. The preparation method according to claim 1, characterized in that: In step S2 and step S3, the first reaction or the second reaction is carried out under the conditions of stirring at 25 to 35° C. for 24 to 48 hours.
7. The preparation method according to claim 1, characterized in that: In step S3, the acid anhydride is maleic anhydride or dimethylmaleic anhydride; the mass ratio of the acid anhydride to the lignin is 1:10 to 1:150; the dialysis bag used in the dialysis has a molecular weight cutoff of 15 kDa, the dialysis fluid used is dimethyl sulfoxide, and the dialysis time is 3 to 5 days; the freeze-drying temperature is -55 to -80°C, and the time is 2 to 3 days.
8. The preparation method according to claim 1, characterized in that: In step S4, the stirring condition is a rotation speed of 200 to 800 rpm, and the dripping time is controlled at 10 to 200 min; in the solution C, the concentration of the lignin-polyallylamine-anhydride coupling is 0.1 to 5 mg / mL; the volume ratio of dimethyl sulfoxide to water is 4:1 to 40; the dialysis, the dialysis bag used has a molecular weight cutoff of 15 to 20 kDa, the dialysate used is water, and the dialysis time is 24 to 72 h.
9. Charge-switchable pH-sensitive lignin-based nanoparticles prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the charge-switchable pH-sensitive lignin-based nanoparticles according to claim 9 in the preparation of antibacterial products.
11. The use according to claim 10, characterized in that: The product is a medicine or a medicine carrier; the antibacterial agent is antibacterial itself or antibacterial biofilm.
12. The use according to claim 10, characterized in that: The bacteria include Escherichia coli, Staphylococcus aureus, Monilia albican, Listeria monocytogenes and Pseudomonas aeruginosa.
Citation Information
Patent Citations
Multi-bioactivity modified lignin self-assembled drug-loaded nano-micelle and preparation method thereof
CN111743862A
Lignin nanoparticles as well as preparation method and application thereof
CN115926206A
Lignin-nano-silver composite antibacterial agent as well as preparation method and application thereof
CN118435941A
pH-responsive amino sodium lignosulphonate as well as preparation method and application thereof
CN104974355A
Charge-transfer nanoparticles and preparation method thereof
CN106511298A